Complete plastome sequence of Xylosma longifolia Clos. (Salicaceae) - Peng Chen; Xiao-Feng Zhang; Jacob B. Landis; Zhi-Xin Zhu; Hua-Feng Wang (Mitochondrial DNA. Part B. Resources, 2021)
Xylosma longifolia is a tree species within Salicaceae and is distributed in Guizhou, Yunnan, Fujian, Guangxi, Guangdong, and Hainan provinces of China as well as in Vietnam, Laos, and India. There are no studies utilizing the complete plastome of Xylosma longifolia in the current literature. Therefore, this report provides a reference for the plastid gene sequence of Xylosma longifolia, and it contributes to the phylogenetic placement and species identification. In this report, we described the complete plastome sequence of Xylosma longifolia. The complete plastome length of Xylosma longifolia is 156,938 bp and has the typical quadripartite structure and gene content of angiosperms, including two inverted repeat (IR) regions of 27,514 bp, a large single-copy (LSC) region of 85,221 bp and a small single-copy (SSC) region of 16,689 bp. The plastome contains 130 genes, including 86 protein coding genes, 36 tRNA genes, eight rRNA genes (5S rRNA, 4.5S rRNA, 16S rRNA, and 23S rRNA). The GC content of the plastome is 36.8%. The complete plastome sequence will be a valuable resource for studies involving the phylogenetic inference of Salicaceae.